(untitled) (Shahid Kirti Multidisciplinary Journal, 2023)
Mobile payment has been a game changer innovation in the financial payment system in the world that has changed the way of life of people. It encourages people to buy and sell goods and services from anywhere using their smart phones. The purpose of the study is to explore the relationship between performance expectancy, effort expectancy, social influence, facilitating condition, hedonic motivation, price value and habit on behavioral intention of people to use mobile payment by using UTAUT2 (Unified Theory of Acceptance and Use of Technology. Quantitative research was carried out for the purpose. Data was collected from 79 valid questionnaires received from respondents came across in Kirtipur area. The data was processed using SPSS 25th version. The findings revealed that there is a significant and positive influence of performance expectancy, effort expectancy, social influence, facilitating condition, hedonic motivation, price value and habit on behavioral intention of people who are using smart phone.